EFEK GAYA ANTAR PARTIKEL DAN DIAMETER PARTIKEL TERHADAP KECEPATAN MINIMUM FLUIDISASI - Febijanto, Irhan (185P -3466)
In this study, the effect of diameter particle and the effect of inter-particle cohesion force due to liquid bridge formation on the minimum fluidization velocity in the fluidized bed have investigated. Also the effect of inter-particle cohesion force on a fluidization condition of the bed has observed by video camera. The investigation results showed bigger diameter can give higher minimum fluidization velocity, and stronger inter-particle force can give higher minimum fluidization velocity, and then make a quality of fluidization of bed lower. Using with this investigation results, the mechanism of fouling and slagging phenomena, which are happen in the coal-fired boiler can be explained.